Study protocol: A randomised trial of the effectiveness of the Common Elements Treatment Approach (CETA) for improving HIV treatment outcomes among women experiencing intimate partner violence in South Africa. Issue 12 (22nd December 2022) - Pascoe, Sophie; Fox, Matthew; Kane, Jeremy; Mngadi, Sithabile; Manganye, Pertunia; Long, Lawrence C; Metz, Kristina; Allen, Taylor; Sardana, Srishti; Greener, Ross; Zheng, Amy; Thea, Donald M; et al.
Abstract : Introduction: Intimate partner violence (IPV) is a barrier to consistent HIV treatment in South Africa. Previous trials have established that the Common Elements Treatment Approach (CETA), a cognitive-behavioural-based intervention, is effective in reducing mental and behavioural health problems but has not been trialled for effectiveness in improving HIV outcomes. This paper describes the protocol for a randomised trial that is testing the effectiveness of CETA in improving HIV treatment outcomes among women experiencing IPV in South Africa. Methods and analysis: We are conducting a randomised trial among HIV-infected women on antiretroviral therapy, who have experienced sexual and/or physical IPV, to test the effect of CETA on increasing retention and viral suppression and reducing IPV. Women living with HIV who have an unsuppressed viral load or are at high risk for poor adherence and report experiencing recent IPV, defined as at least once within in the last 12 months, will be recruited from HIV clinics and randomised 1:1 to receive CETA or an active attention control (text message reminders). All participants will be followed for 24 months. Follow-up HIV data will be collected passively using routinely collected medical records. HIV outcomes will be assessed at 12 and 24 months post-baseline. Questionnaires on violence, substance use and mental health will be administered at baseline, post-CETA completion and at 12 months post-baseline. Our primary outcome is retention and viral suppression (<50 copies/mL) by 12 months post-baseline. We will include 400 women which will give us 80% power to detect an absolute 21% difference between arms. Our primary analysis will be an intention-to-treat comparison of intervention and control by risk differences with 95% CIs. Ethics and dissemination: Ethics approval provided by University of the Witwatersrand Human Research Ethics Committee (Medical), Boston University Institutional Review Board and Johns Hopkins School Institutional Review Board. Results will be published in peer-reviewed journals. Trial registration number: NCT04242992 .